Lactoferrin in Gingival Crevicular Fluid and Peripheral Blood during Experimental Gingivitis - Ozdemir, Burcu; Ozcan, Gonen; Karaduman, Burcu; Teoman, Aslı Idil; Ayhan, Eylem; Ozer, Nazmi; Us, Durdal (European Journal of Dentistry, 2009)
Objectives: Lactoferrin (LF) is an iron binding protein and stored in the specific granules of granulocytes. It is released by degranulation following granulocyte activation. A positive correlation was previously reported between periodontitis and LF titers of gingival crevicular fluid (GCF) and blood. The purpose of this study was to examine alterations of GCF and blood levels of LF (LF-GCF and LF-BL, respectively), employing the experimental gingivitis model.Methods: Twelve systemically healthy volunteers, aged 19-21, were selected. Pre-experimental phase of hygiene was followed by a 14-day experimental gingivitis phase in which subjects refrained from all oral hygiene procedures. After that subjects resumed optimal plaque control for 21 days of recovery period. At days 0 (baseline), 14 and 35 gingival crevicular fluid (GCF) and blood samples were collected and plaque index (PI), gingival index (GI), bleeding on probing (BOP) and probing pocket depth scores were recorded. LF levels were measured with commercial enzyme-linked immunosorbent assay (ELISA) kit.Results: PI, GI, BOP and LF-GCF increased significantly after 14 days of experimental gingivitis period and decreased significantly after reinstitution of oral hygiene measures (P<.05). LF-BL appeared to follow the same pattern. Significant negative correlation was detected between the level of LF-BL and BOP at day 14 (P<.05), whereas significant positive correlation was noticed between LFBL and clinical scores PI, GI and BOP at day 35 (P<.05).Conclusions: LF-BL followed the same pattern with LF-GCF and clinical scores during the experimental gingivitis and recovery periods, although alterations of the LF-BL appeared statistically insignificant. (Eur J Dent 2009;3:16-23)
Keywords: Lactoferrin; Gingival crevicular fluid; Gingivitis; Peripheral blood; Periodontal index